172k views
2 votes
4 (-3x - 1) = 13x + 6

2 Answers

7 votes

Answer: x=-0.4 or -2/5

Explanation:

Distribute: 4 (-3x-1)=13x+6

Add 4: -12x-4=13x+6

Subtract -13x: -12x=13x+10

Divide by -25: -25x=10

x= 2/5

or

x=-0.4

Hope this helps ma dude!!

User Titanous
by
5.3k points
4 votes

Answer:

x=-2/5

Explanation:

4(-3x-1)=13x+6 ~ Distribute the 4 into the parenthesis

-12x-4 = 13x+6 ~ add 12x to both sides

-4= 25x + 6 ~ subtract 6 from both sides

-10 =25x ~ divide by 25

-10/25 = x ~ simplify the fraction by dividing the num. and den by 5

-2/5 =x

User Biox
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.